(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
The main objective of the research work was to improve the solubility of Bosentan by preparing Microemulsion (ME) for pulmonary artery hypertension therapy. Capmul MCM C8 was selected as oil, Tween 20 as a surfactant and Transcutol HP as a co-surfactant. From Pseudoternary phase diagram ratio of Smix (1:1) selected. From the Microemulsion area of ternary diagram different batches were prepared, but the drug was precipitate from the formulation which can be avoid by adding precipitate inhibitor. Pluronic F 127 was utilized as precipitate inhibitor in the concentration of 1.5%. The optimized formulation ME 8 contain oil (30 %V/V), Smix (60 %V/V) and water (10 %V/V). The prepared Microemulsion evaluated for globule size 96.71±0.11 nm, % transmittance 99.45±0.54 % and >99 % drug content. TEM confirm the spherical shape of globule. The physicochemical parameter of ME 8 was performed and to enhance the stability of Microemulsion it is converted in to solid ME by using adsorbent. Aeroperl 300 was selected as an adsorbent in the drug to adsorbent ratio (1:0.5 %W/W) based on physicochemical properties. From the in-vitro drug release investigation after 7 hours %CDR of ME 8 was found to be 78.87±0.17% and solid Microemulsion (SME 3) shows 76.83±0.29%. The pure drug shows only 27.63±0.23% CDR, which indicate that ME revealed better drug release than pure drug. There was a 2.8 fold increases in solubility compare to pure drug. From the In-vivo data compared to convention formulation, there was significant change in pharmacokinetics data observed.